The role of serum methylglyoxal on diabetic peripheral and cardiovascular autonomic neuropathy: the ADDITION Denmark study - Hansen, Christain, Stevns; Nawroth, Peter Paul; Fleming, Thomas (Diabetic medicine, 2015)
Aims: Cardiovascular autonomic neuropathy and diabetic peripheral neuropathy are common diabetic complications and independent predictors of cardiovascular disease. The glucose metabolite methylglyoxal has been suggested to play a causal role in the pathogeneses of diabetic peripheral neuropathy and possibly diabetic cardiovascular autonomic neuropathy. The aim of this study was to investigate the cross-sectional association between serum methylglyoxal and diabetic peripheral neuropathy and cardiovascular autonomic neuropathy in a subset of patients in the ADDITION-Denmark study with short-term screen-detected Type 2 diabetes (duration ~ 5.8 years). Methods: The patients were well controlled with regard to HbA1c, lipids and blood pressure. Cardiovascular autonomic neuropathy was assessed by measures of resting heart rate variability and cardiovascular autonomic reflex tests. Diabetic peripheral neuropathy was assessed by vibration detection threshold (n = 319), 10 g monofilament (n = 543) and the Michigan Neuropathy Screening Instrument questionnaire (n = 966). Painful diabetic neuropathy was assessed using the Brief Pain Inventory short form (n = 882).Results: No associations between methylglyoxal and cardiovascular autonomic reflex tests or any measures of diabetic peripheral neuropathy or painful diabetic neuropathy were observed. However, a positive association between methylglyoxal and several heart rate variability indices was observed, although these associations were not statistically significant when corrected for multiple testing. Conclusion: Serum methylglyoxal is not associated with cardiovascular autonomic neuropathy, diabetic peripheral neuropathy or painful diabetic neuropathy in this cohort of well-treated patients with short-term diabetes.